BS EN IEC 61010-2-033 AMD AA. Safety requirements for electrical equipment for measurement, control, and laboratory use. Part 2-033. Particular requirements for hand-held multimeters and other meters for domestic and professional use, capable of measuring mains voltage (25th September 2020) - British Standards Institution,
No abstract available